WANPRESTASI DALAM PERJANJIAN TERAPEUTIK PROGRAM BAYI TABUNG (IN VITRO FERTILIZATION) YANG MENGAKIBATKAN KERUGIAN PASIEN - Alivia Febriyanti (2023)
Sometimes a marriage has problems in getting offspring. The development of IVF (In Vitro Fertilization) medical technology is a hope for couples who have never had children. Therapeutic agreements made before carrying out IVF aim to prevent losses between the parties making the agreement. This type of research is normative juridical by examining laws and regulations that are in accordance with the problems of this research. The results of the study are that therapeutic agreements that harm patients are formed from doctors' mistakes and negligence in providing health services. The doctor's actions were categorized as a default described in Article 1236 and Article 1239 of the Civil Code. Patients can file lawsuits if the doctor is proven to have committed a default and is supported by concrete evidence due to the abuse of the doctor's authority. The form of compensation proposed as a result of default is something that is borne by the debtor due to non-fulfillment of the contract agreed upon according to Article 1243 of the Civil Code. In carrying out their profession, doctors want to comply with the medical code of ethics in accordance with Article 24 paragraph (1) of Law Number 36 of 2009, it is necessary to review the medical code of ethics, especially monitoring the actions of doctors. in fulfilling the therapeutic agreement.